Indonesia Universal Health Coverage Implementation on University Students - Adityo Pratikno Ramadhan; Budiyono Budiyono; Djonet Santoso (Journal of Government and Civil Society, 2020)
This research aimed to investigate the percentage of university students at the University of Bengkulu, Indonesia, who participated in the national health insurance program, and why the students did or did not participate in the national health insurance program. This research was performed with the inductive approach and sampled 366 university undergraduate students from eight faculties at the University of Bengkulu, Indonesia. The data collection was conducted by survey technique using a questionnaire. The results show that only 58.2% of university students who participated in the national health insurance program and their parents played an important role in determining whether they participated in the program. Pseudo universal health coverage would probably happen in Indonesia since some students participated in the national health insurance program. However, their premium payments were overdue, so that their insurance coverage became inactive. The unique finding of this research is that 1.96 percent of students mentioned that they did not participate in the national health insurance program because they perceived this program categorized as usury, which is forbidden in Islam. Penelitian ini bertujuan untuk mengetahui persentase mahasiswa Universitas Bengkulu yang mengikuti program jaminan kesehatan nasional, dan mengapa mahasiswa mengikuti atau tidak mengikuti program jaminan kesehatan nasional. Penelitian ini dilakukan dengan pendekatan induktif dan mengambil sampel 366 mahasiswa sarjana dari delapan fakultas di Universitas Bengkulu, Indonesia. Pengumpulan data dilakukan dengan teknik survei menggunakan kuesioner. Hasil penelitian menunjukkan bahwa hanya 58,2% mahasiswa yang mengikuti program jaminan kesehatan nasional dan orang tuanya yang berperan penting dalam menentukan keikutsertaan mereka dalam program tersebut. Pertanggungan kesehatan universal semu mungkin akan terjadi di Indonesia karena beberapa pelajar berpartisipasi dalam program jaminan kesehatan nasional. Namun, pembayaran premi mereka terlambat, sehingga pertanggungan asuransinya menjadi tidak aktif. Temuan unik dari penelitian ini adalah 1,96 persen mahasiswa menyatakan tidak mengikuti program jaminan kesehatan nasional karena menganggap program ini termasuk riba yang dilarang dalam Islam.